Multilayer laminated Cu coil/CaO–Li2O–B2O3–SiO2 glass-ceramic preparation via a novel insulation packaging strategy for flat wire motor applications - Haitao Zhu; Yanyu Song; Guangyou Pan; Naibin Chen; Xiaoguo Song; Long Xia; Duo Liu; Shengpeng Hu (Nano Materials Science)
A new insulation packaging strategy for the stator windings of flat wire motors based on LTCC technology was studied for the first time. The study aimed to replace traditional plastic packaging methods and avoid aging issues by fabricating a novel multilayer laminated Cu coil/CaO–Li2O–B2O3–SiO2 glass-ceramic structure. The analysis of the interface microstructure of the laminated structure revealed that the CaO–Li2O–B2O3–SiO2 glass-ceramic matrix consisted of a crystalline phase of CaSiO3 and an amorphous phase of SiO2. The interface between the Cu coil and CaO–Li2O–B2O3–SiO2 glass-ceramic exhibited good bonding with no formation of secondary phases. Additionally, the strong bonding between the Cu coil and CaO–Li2O–B2O3–SiO2 glass-ceramic was attributed to the diffusion of Cu atoms at the interface. The novel multilayer laminated structure based on LTCC technology proposed in this study can help achieve high-reliability insulation packaging for the stator windings of future high-power density and miniaturized flat wire motors.